Implementasi Metode Agile Development pada Pengembangan Aplikasi Pemantauan Tingkat Stres Kerja Berbasis Mobile - Putra Afiqi; Sri Wulandari (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2025)
This study aims to develop the WARASPADA (Work Stress Awareness and Prevention Application Dashboard) as a mobile-based work stress monitoring tool using the Agile Development methodology, with the Flutter framework for the frontend and Supabase as the backend. The instrument used in this research is the Work Stress Diagnosis Survey (SDS) issued by the Indonesian Ministry of Manpower. System evaluation was conducted using the Technology Acceptance Model (TAM), which measures four key variables: Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Attitude Toward Using (ATU), and Behavioral Intention to Use (BIU). The results show that the overall user acceptance level reached 85.4%, categorized as very good. This finding indicates that users perceive the application as easy to use, functional, and effective for detecting and monitoring work stress levels. Therefore, the WARASPADA application is considered feasible and has strong potential to be implemented in workplace environments as a data-driven decision-support tool for human resource management.